2020
DOI: 10.1177/2158244020934489
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Positive Labor Market Mobility

Abstract: The present article proposes a new labor market index, called the positive labor market mobility index, which focuses on quantifying the amount of “desired” labor market mobility present in the transitions of young individuals, providing a useful way of comparing countries on that matter. Well-established indices in the literature aiming at measuring mobility take into account all movements among states and/or the diagonal elements of the transition probability matrix that denote immobility. On the contrary, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…From the information in the transition matrix, it is possible to construct indexes that summarize the degree of fluidity and immobility in the society from which the transition matrix was calculated. Among these indexes, I consider the Prais-Shorrocks index (Prais, 1955;Shorrocks, 1978) and the immobility index (Symeonaki and Stamatopoulou, 2020).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…From the information in the transition matrix, it is possible to construct indexes that summarize the degree of fluidity and immobility in the society from which the transition matrix was calculated. Among these indexes, I consider the Prais-Shorrocks index (Prais, 1955;Shorrocks, 1978) and the immobility index (Symeonaki and Stamatopoulou, 2020).…”
Section: IImentioning
confidence: 99%
“…The immobility index (𝐼𝑀 𝑀 𝑜.𝑐 ), as defined by Symeonaki and Stamatopoulou (2020), is the share that rank persistence represents out of the total number of ranks considered in the transition matrix. This ratio is the rate at which a member of society is expected to persist at any given rank.…”
Section: IImentioning
confidence: 99%
“…The development of a set of indicators that will aid the measurement and the identification of precarious workers is currently a central matter at the European level, hindered by the lack of an agreed definition of precarious employment [1]. However, precarity is recognised as a multidimensional construct encompassing dimensions of employment insecurity, integrating both types of contract and perceptions of job insecurity, relations between workers and employers, low earnings, poverty, and deprivation, limited employment rights and social security protection, and incapacity to exercise legally granted employment rights ( [2], [3], [4], [5], [6], [7], [8], [9], [10], [11]). The existing literature has revealed that women, young people, and migrants must overcome greater difficulties to find a secure and stable employment, facing higher risk of precariousness and in-work poverty ( [12], [13], [14]).…”
Section: Introductionmentioning
confidence: 99%